Relações de Arbitrariedade e Iconicidade na composição dos sinais em Libras - Constâncio, Rosana de Fátima Janes (2022)
In Brazil, research related to the Brazilian Sign Language (Libras, in portughese) has been increasingly intensified, notably after its recognition as a "means of communication and expression" (Federal Law No. 10.436/02, Article 1). The advances made in the field of linguistic studies and educational practices involving Libras and the needs demanded by Brazilian deaf students/students have been remarkable. Nevertheless, there are still many questions about the language that need to be deepened; one of them concerns the nature of the signs that make up its lexicon. Motivated by the fact that Libras is a sign language, visual and spatial, there are many who defend the idea that these signs are iconic, since many of them do in fact refer to the referents they name. However, this kind of statement does not hold, and several studies have shown that. The subject of iconicity, therefore, is the object of study of this thesis. In order to deepen it, the goal of this thesis was not only to rescue the theoretical aspects related to the iconicity present in languages, whether oral or sign languages, but, above all, to understand the continuum from iconicity to arbitrariness. Four central questions guided this research: (i) How are the relations of formation of signs in Libras?; (ii) Based on the results obtained in (i), is it possible to say that Libras signs are only iconic or arbitrary as generally advocated by many? (iii) Can Libras signs also assume other levels? (iv) Assuming that, according to the specialized literature (KLIMA; BELUGGI, 1979; PERNISS; VIGLIOCCO, 2014; ORTEGA, 2017), besides the iconic and arbitrary relationship, there are two other levels where the lexical items of a language can be distributed, how does this arrangement occur in Libras? To answer these questions, we relied on theoretical assumptions advocated by Descriptive Linguistics (STOKOE, 1960; FERREIRA-BRITO, 1990, 2010; PERINI,2010) and by lexical studies (CABRÉ, 1998). The data for analysis were extracted initially from the work Iconographia dos Signaes dos Surdos-Mudos (GAMA, 1875), in all, 407 signs and their referents that were contrasted in three other works (OATES, 1969; SOCIEDADE TORRE DE VIGIA, 1992; CAPOVILLA et al., 2001). However, for the analysis, we considered only the work with the most updated version: Dicionário da Língua de Sinais do Brasil: a Libras em suas mãos (CAPOVILLA et al., 2017). The results obtained from this investigation process confirmed our initial hypotheses that there are two other possible levels in Libras, the translucent and the obscure, which may fit the continuum of linguistic phenomena from iconicity to arbitrariness.